Pasar Bebas di Era Globalisasi dalam Perspektif Ekonomi Syariah - Hoddemah Hoddemah; Wiwik Saidatur Rolianah (Maliyah : Jurnal Hukum Bisnis Islam, 2018)
The free market in the era of globalization is a necessity that cannot avoid. Countries that cannot meet their own needs must trade with other countries to meet these lacking needs. This free market is expected to improve the economy of a country and the welfare of its people. Still, in subsequent developments, the free market will positively impact the perpetrators and have a negative effect so that there will be contraception among economists regarding the merits and demerits of the free market. So far, a country can't stay away from the free market so how a country must make innovation, creativity, work levels, and everything good and quality so that its merchandise can compete in the free market. In Islamic economics, the existence of a free market is allowed to meet the needs of a country while still paying attention to the principles of trade in Islam such as being honest and not doing things that are contrary to religious teachings such as monopoly.